Veterinary and pet owner perspectives on addressing access to veterinary care and workforce challenges - Niemiec, Rebecca; Champine, Veronica; Frey, Danielle; Lobdell, Allyce; Steele, Apryl; Vaiden, Claire; Kogan, Lori; Mertens, Andrew (Frontiers in Veterinary Science, 2024)
Objectives (1) Assess and compare the perceptions of pet owners and veterinary professionals pertaining to the extent of veterinary workforce and access to care challenges in 2023 in Colorado, and (2) Assess what programs, policies, and resources veterinary professionals and pet owners believe would be most effective at addressing access to care and workforce challenges in Colorado. Sample 736 veterinarians, veterinary technicians, or practice/owner manager (“veterinary professionals”) in Colorado. A total of 1,209 pet owners (919 from an online survey and 290 from in-person surveying). Procedures Distribution of an online anonymous survey to veterinary professionals in Colorado. Pet owners were surveyed both online and in-person at pet pantry or shelter events. Results Veterinary professionals reported significant workforce challenges, including having to frequently divert clients, clients forced to decline medical care or having to euthanize their pets due to cost. Veterinary professionals were especially supportive of policy efforts to enhance recruitment and retention of technicians, including through mechanisms such as clarifying their scope of practice, loan repayment programs, and enhancing career pathways. Colorado pet owners’ responses pertaining to the scope of access to care challenges were similar to prior national research. Pet owners reported particularly needing low-cost emergency clinics in their community as well as resources to reduce the cost of care. Pet owners were generally supportive of expanding veterinary care access through telemedicine; indicating they would feel comfortable seeing a veterinarian via telemedicine, even for the first time, and that expanded use of telemedicine would increase their ability to obtain care. Conclusions and clinical relevance Colorado pet owners and veterinary professionals both identified numerous access to care challenges as well as indicated support for the development of several potential initiatives to address the problem. Low-cost clinics that provide sick and emergency care was the resource rated as being most helpful among pet owners. Further exploration of grants, voucher programs, expansion of telemedicine, increased utilization and title protection for CVTs, and the creation of the veterinary professional associate position are all initiatives that were noted to be worthy of further exploration.